A Superhydrophobic Surface Templated by Protein Self‐Assembly and Emerging Application toward Protein Crystallization. Issue 3 (26th November 2015) - Gao, Aiting; Wu, Qian; Wang, Dehui; Ha, Yuan; Chen, Zhijun; Yang, Peng
Abstract : A proteinaceous superhydrophobic material for facile protein crystallization is reported. The lysozyme phase transition is rationally manipulated to form a reliable superhydrophobic coating on virtually arbitrary material surfaces with good thermostability and mechanical robustness. Such a surface exhibits a fascinating capability to drive protein crystallization, and the protein crystal array can be facilitated in a large area at an ultralow protein concentration.